2022
DOI: 10.3390/biom12020246
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Marine Alkaloid Lepadin A as Potential Inducer of Immunogenic Cell Death

Abstract: Natural products and their synthetic analogs and derivatives are a traditional source of bioactive molecules with potential development as drug candidates. In this context, Marine Natural Products (MNPs) represent a rich reservoir of diverse molecular skeletons with potential pharmacological activity that, so far, has been mostly explored in cancer and infectious diseases. Starting from the development of a novel bioassay-guided screening platform for immunomodulatory compounds from an in-house MNPs library, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…Lately, we have identified by bioassay-guided fractionation the alkaloid lepadin A (45) from the tunicate Clavelina lepadiformis sp. B, already known to exhibit significant in vitro cytotoxicity against several human cancer cell lines, as a potent activator of innate immune cells [189]. In this study, lepadin A showed both cytotoxic effect against chronic forms of lung carcinoma, melanoma, and multiple myeloma cells together with maturation of mouse dendritic cells at micromolar concentrations.…”
Section: Compounds From Marine Environmentmentioning
confidence: 49%
See 1 more Smart Citation
“…Lately, we have identified by bioassay-guided fractionation the alkaloid lepadin A (45) from the tunicate Clavelina lepadiformis sp. B, already known to exhibit significant in vitro cytotoxicity against several human cancer cell lines, as a potent activator of innate immune cells [189]. In this study, lepadin A showed both cytotoxic effect against chronic forms of lung carcinoma, melanoma, and multiple myeloma cells together with maturation of mouse dendritic cells at micromolar concentrations.…”
Section: Compounds From Marine Environmentmentioning
confidence: 49%
“…Moreover, the immune response of 45 occurs at subtoxic concentrations (EC 50 = 1.64 µg/mL; IC 50 = 4.20 µg/mL), indicating that the molecule can induce a cell stress. On this basis, even though further studies are needed to investigate the mechanism of action, it was suggested that lepadin A could act as ICD inducer [189].…”
Section: Compounds From Marine Environmentmentioning
confidence: 99%
“…These preliminary results of biological activities suggest a great potential for developing lepadins as a new class of medicines. However, the in-depth investigation of the biological functions of lepadins, in particular, their mechanism of action, remains rare and challenging, , partially due to the unavailability of these rare marine natural products. To address the supply of materials, we have developed a novel synthetic strategy for the efficient construction of the highly functionalized cis -fused DHQ core on multigram scale, which led to a collective total synthesis of seven members of lepadins (Supporting Information Figure S1) .…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that lepadin A was previously reported to be cytotoxic against cancer cells with maturation of mouse dendritic cells at micromolar concentrations. 62 The combination of these two effects is expected to improve anticancer efficacy through a synergistic mechanism derived from both the role of mature dendritic cells in the generation of anti-tumor activity and the release of immunogenic molecules by dying cells. Unfortunately, at this moment, we were not able to in vivo study the immunogenic response of lepadin H.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the development of an innovative screening platform for the identification of immunomodulatory compounds [ 16 ], we have recently reported that lepadin A ( 1 ) shows a cytotoxic effect in a panel of cancer cell lines along with the ability to induce maturation of mouse dendritic cells (DCs). The combination of this activity led us to put forward a potential role as ICD inducer for this natural product [ 17 ].…”
Section: Introductionmentioning
confidence: 99%